2009
DOI: 10.3748/wjg.15.4075
|View full text |Cite
|
Sign up to set email alerts
|

An adult case of celiac sprue triggered after an ileal resection for perforated Meckel’s diverticulum

Abstract: Celiac disease can be triggered by upper abdominal surgery, such as vagotomy, oesophagectomy, pancreaticoduodenectomy, and gastrojejunal anastomosis. Here we report a case of a 24 year-old woman who developed celiac disease after an ileal resection for perforated Meckel's diverticula. This is the first reported celiac case that has been triggered, not by upper abdominal surgery, but after ileal resection for Meckel's diverticula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…A search in the literature revealed 24 cases of CeD that were discovered after upper GI surgery, of which ten occurred after pancreaticoduodenectomy (Table 2). [9][10][11][12][13][14][15][16] Remarkably, all those cases presented with marked weight loss, just as in our patient. Ours is the oldest patient described in the literature to develop CeD after upper GI surgery.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…A search in the literature revealed 24 cases of CeD that were discovered after upper GI surgery, of which ten occurred after pancreaticoduodenectomy (Table 2). [9][10][11][12][13][14][15][16] Remarkably, all those cases presented with marked weight loss, just as in our patient. Ours is the oldest patient described in the literature to develop CeD after upper GI surgery.…”
supporting
confidence: 61%
“…8 Several reports have suggested that various surgical interventions, particularly upper gastrointestinal (GI) operations such as gastrectomy, Nissen fundoplication and Roux-en-Y gastric bypasses, may unmask undiagnosed CeD. [9][10][11][12][13][14][15][16] In this report we described a patient diagnosed with CeD following a pylorus-preserving pancreaticoduodenectomy (PPPD). Before surgery there was no clue as to the presence of CeD.…”
mentioning
confidence: 99%
“…16,17 Subsequently, however, unmasking has been described after a wide variety of procedures, both intra-abdominal and extra-abdominal. 9,10,[18][19][20][21] A more likely explanation is perioperative stress, which leads to activation of celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent evaluation then leads to the diagnosis, termed "unmasking" [6]. Initial reports of this phenomenon occurred following upper gastrointestinal procedures such as fundoplication and gastrectomy [6]; however, unmasking has been subsequently described following a variety of intraabdominal and extraabdominal procedures [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%